Profiting from the digitalisation of colonial cultural objects: A comparison of British and Dutch museum practice - Kamardeen, N.; Nanayakkara, T. (University of Colombo, 2025)
Colonial cultural objects can be described as cultural objects removed from a country during the era of European colonial expansion, often without the permission of the source country, and almost always without the payment of compensation. Museums of the former colonisers have long benefited financially from the physical objects themselves, through the collection of fees as entrance tickets from visitors. In addition, digital images, either as photographs or as 3-D images, that have been generated by these institutions from such objects, also raise revenue and have the potential to continue generating income for the institution even after the object has been returned to the source country. This problem for source countries that are requesting the return of colonial cultural objects is viewed from a case study concerning the statue of Tara, originally from Sri Lanka, and now at the British museum. The publishers of a research article on Tara, authored by a Sri Lankan researcher, had to pay a sum of 45 euro to the British museum in order to be able to publish an image of the statue of Tara in the publication...
Keywords: Colonial cultural objects; British museum; Dutch museums; Digitalisation; Copyright; Ownership